A most diabolical deed': Infanticide and Irish society, 1850-1900. (Oxford University Press USA, 2015)
Examining the phenomenon of infanticide in Ireland from 1850 to 1900, this title is based on a large sample of 4,645 individual cases of infant murder, attempted infanticide and concealment of birth. Through a variety of sources, attitudes towards the crime of infanticide and women accused of the offence are revealed.